Pre-meal high-performance inulin supplementation reduce post-prandial glycaemic response in healthy subjects: A repeated single-arm clinical trial - Wijaya, Hendy; Tjahjono, Yudy; Foe, Kuncoro; Setiadi, Diga Albrian; Kasih, Elisabeth; Wihadmadyatami, Hevi (Elsevier Ltd, 2022)
Background and aims: High-performance (HP) inulin, a dietary fiber consists of more than 10 fructose polymers, have been shown to reduce post-prandial glycaemic response (PPGR) and could prevent the occurrence of Type-2 diabetes mellitus (T2DM). Currently, there are no data on whether pre-meal HP inulin supplementation could decrease PPGR. Methods: 8 healthy adults consumed 20 g of formula that contain 60.2 inulin (w/w) dissolved in water. Blood glucose was measured in fasted participants and at 30–120 min after starting to eat a prepared meal. This test was repeated every week with different supplement formulas. Conclusion: pre-meal HP Inulin formula supplementation could suppress the post-prandial glycaemic response. © 2021 Diabetes India